Health advertising: prevention for profit. - Freimuth, V S (1988)
The National Cancer Institute (NCI) estimates on the basis of current knowledge alone that, at a minimum, 30,000 lives could be saved in the year 2000 if Americans would modify their dietary habits. A recent innovative way of responding to this challenge was the Kellogg Company/NCI All-Bran advertising campaign. This paper will describe the campaign, and its impact on consumers, cereal industry sales, food industry advertising practices, health regulatory policy, and the organizational credibility of both NCI and Kellogg. For the past three years, Kellogg has included NCI's cancer prevention messages in their advertisements for All-Bran cereal and on their bran cereal boxes. This collaborative effort has stimulated considerable controversy over whether the health claims made on the cereal label are in violation of federal food labeling regulations. Meanwhile, research has demonstrated the positive impact of the campaign on consumer's knowledge and behavior regarding fiber as well as on Kellogg's profits. Other manufacturers are anxious to jump on the "branwagon"; however, many unanswered questions remain about this new approach to health advertising.